The Transcendental Imagination: a Faculty in Exile: Heidegger’s Interpretation of Kant (Balthazar, 2025)
In Heidegger’s reading of Kant, the transcendental imagination takes on a fundamental role. Imagination comes forth as the common root of both sensibility and understanding, carrying out its function by opening the intellect to sensibility. It can carry out this task insofar as it is temporality; within this horizon, Kantian synthesis is rethought as a temporal ecstatic synthesis. Imagination is thus taken up as the primordial ground of all transcendental elements, thereby pointing to an original unity of spontaneity and receptivity. As a result of this perspective, the transcendental imagination cannot be pinned down to either sensibility or understanding; it stands as a faculty without a homeland, Heimatlos, a faculty in exodus.